2018
DOI: 10.1016/j.apsb.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A novel nitroreductase-enhanced MRI contrast agent and its potential application in bacterial imaging

Abstract: Nitroreductases (NTRs) are known to be able to metabolize nitro-substituted compounds in the presence of reduced nicotinamide adenine dinucleotide (NADH) as an electron donor. NTRs are present in a wide range of bacterial genera and, to a lesser extent, in eukaryotes hypoxic tumour cells and tumorous tissues, which makes it an appropriate biomarker for an imaging target to detect the hypoxic status of cancer cells and potential bacterial infections. To evaluate the specific activation level of NTR, great effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…1 H NMR (400 MHz, DMSO-d 6 ): δ 1.33 (t, J = 7.09 Hz, 3 H), δ 4.37 (q, J = 7.09 Hz, 2 H), δ 8.08−8.19 (m, 2 H), δ 8.23 (dd, J = 10.51, 1.71 Hz, 1 H). 19 F NMR (376 MHz, DMSO-d 6 ): δ −106.99 (s, 1 F).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…1 H NMR (400 MHz, DMSO-d 6 ): δ 1.33 (t, J = 7.09 Hz, 3 H), δ 4.37 (q, J = 7.09 Hz, 2 H), δ 8.08−8.19 (m, 2 H), δ 8.23 (dd, J = 10.51, 1.71 Hz, 1 H). 19 F NMR (376 MHz, DMSO-d 6 ): δ −106.99 (s, 1 F).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…9 We were in particular interested in investigating activatable molecular probes for the detection of nitroreductases (NTRs) in bacteria. [10][11][12][13][14][15] NTRs represent a family of avin-containing enzymes that are able to effectively metabolize nitrosubstituted groups into hydroxylamines or amines in the presence of reduced nicotinamide adenine dinucleotide (NADH) or nicotinamide adenine dinucleotide phosphate (NADPH). 16 NTRs are widely expressed in most Gram-positive and Gramnegative bacterial strains, but also in hypoxic tumour cells and tumorous tissues of eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia changes the tumor microenvironment through the overexpressed HIF-1 α , which leads to the cancer progression and metastasis 38 , 39 . It has been reported that the azobenzene group could be cleaved with the elevated levels of reducing enzymes in hypoxic tumor microenvironment 40 .…”
Section: Resultsmentioning
confidence: 99%